The Superlative Scale S of Butcher and Han (1995): the "fake-good" in the Spanish adaptation of the MMPI-2 - Sánchez Crespo, Guadalupe (Pontificia Universidad Católica del Perú, 2003)
The present study investigated the '"fake-good" behaviour using the Superlative Scale S in theSpanish adaptation of the MMPI-2. From the 3.035 participants, the "normal" group ( 1.723)and the "clinic" group (561) responded with sincerity lo the questionnaire. A group of 269"'normal" participants was asked to show a negative image of themselves (group "fake-bad"')and other 282 participants, to show a positive image (group "Fake-good"); finally a group of 200 participants answered to the questionnaire without following the information of the items (group "inconsistent answers"'). The results showed the sensibility of this to detect the individuals that falsify their answers trying to present their more positive image. There were difficulties to identify individuals who answered to the questionnaire without keeping in mind the information of the items.